Edukasi Stunting pada Ibu Balita - Heni Heryani; Istikharoh Istikharoh; Meylinda Sari; Mirna Yulansari; Monica Putri Gustin (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction The prevalence of stunting in Indonesia in 2022 is 21.6%, while in Ciamis in 2021 it is 16%, this figure has not reached the national target of 14%. This is a very serious problem that needs to be dealt with quickly and precisely. One of the factors causing stunting is the lack of knowledge about efforts to prevent stunting from an early age. The impact of stunting is very dangerous for the survival of children in the future. One of the efforts to prevent stunting that can be done is to provide education about efforts to prevent stunting. Objective: The purpose of this community service is to increase the knowledge of mothers of toddlers about stunting, with the target of mothers of toddlers who come to Posyandu Dusun Desa Kulon, Cijeungjing Ciamis. Method: The method used in this service is the provision of education about stunting through the media of leaflets. Results: The results of the service show that the average pretest result is less knowledgeable by 65%, and after education, the average knowledge is sufficient by 60.5%. Conclusion: Stunting education using leaflet media can increase the knowledge of mothers under five as an effort to prevent stunting.